Morphological and genetic characterisation of seahorse species (Syngnathidae: Hippocampus spp.) in the Waters of Sabah, Malaysia. - Parivaseni Ravichandran; Chen, Cheng Ann; Soo, Chen Lin; Nur Fatihah Abd Halid; Raymie Nurhasan; Teng, Sing Tung (Universiti Malaysia Sabah, 2025)
Seahorse are teleosts belonging to the genus Hippocampus which consists of 57 species. Among the 57 species, only 12 species exist in Malaysian waters and 11 species in the coastal waters of Sabah. These records and checklists pre-date 2015, and no known studies or field surveys have been conducted in Sabah since then. In this study, a field survey was conducted in selected areas of Sabah waters to document the species composition through morphological and genetic identification. Out of the 11 species that were recorded previously, only two species (Hippocampus barbouri and Hippocampus comes) were found and identified using taxonomic keys. CO1 mitochondrial gene was used for genetic identification and phylogenetic tree reconstruction of Maximum Likelihood (ML). The dataset comprises sequences of 11 species from Malaysian waters (excluding H. satomiae). The genetic distances, i.e., p-distances, for H. barbouri and H. comes were recorded to be less than 1% inter-species and more than 10% intra-species, which confirmed the distinct species genetically. Furthermore, findings highlight the urgency of implementing conservation strategies to protect the remaining populations, in light of limitations of this study.